Effect of subclinical infection of Salmonella Typhimurium on the productive parameters in the production of fattening guinea pigs (Cavia porcellus) - Bazán R., Víctor (2020)
The effect of Salmonella Typhimurium was determined on the productive parameters of guinea pigs (Cavia porcellus). Forty recently weaned male guinea pigs fed with a base diet were used. The animals were distributed in four treatments with 10 repetitions each were used. T1: saline solution (control); T2: saline + AGP (antibiotic growth promoter antibiotic); T3: challenge with Salmonella Typhimurium; T4: challenge with Salmonella Typhimurium + AGP. Dosing with saline or with an infective dose of Salmonella Typhimurium (2 x 106 CFU) was made on day 11 of the study. Bodyweight gain, feed consumption, feed conversion, carcass yield and economic gain were evaluated. Samples were taken from organs and meat after the slaughtering for the microbiological analysis. Animals challenged with Salmonella (T3 and T4) showed lower bodyweight gain, higher feed intake and poorer feed conversion compared to guinea pigs of T1 and T2 (p<0.05). The carcass yield was similar in the four treatments, while the economic gain in guinea pigs of T3 and T4 was affected by 28-30%. Salmonella was isolated from 2 lung samples and one spleen sample in animals from T1, while the pathogen could be isolated in more than 50% of the samples in animals of T3 and T4. Only four samples with Salmonella in the meat were detected (T3). It is concluded that the productive parameters and the economic retribution in guinea pigs are negatively affected by subclinical infection with Salmonella Typhimurium.